(untitled) (Western European Journal of Medicine and Medical Science, 2025)
This article explores the pathogenesis and etiology of tinnitus, with a particular focus on the adverse impact of occupational environments. Industrial noise, mechanical vibration, exposure to ototoxic chemicals, and workplace-related psychosocial stressors are analyzed as contributing factors to the development and exacerbation of tinnitus symptoms. Drawing on contemporary epidemiological data, the prevalence of tinnitus among industrial workers is examined, along with associated hearing impairments. The review further highlights international best practices for prevention, including occupational safety standards, auditory health monitoring, and the use of personal protective equipment. Special emphasis is placed on the importance of early diagnosis, workplace hygiene, and long-term auditory risk mitigation strategies